Biochar usefulness in achieving goals of carbon farming and sustainable agricultural systems - Berbeć, Adam Kleofas; Wyzińska, Marta; Berbeć , Tytus (Polish Journal of Agronomy, 2024)
This paper presents an overview of the literature research on the benefits of biocarbon (biochar) as an important part of sustainable agriculture and carbon farming. The main objective was to familiarise the reader with the literature findings on the effects of biocarbon application on the environment, soil, soil organic mater, soil microorganisms, and impact on crop yields. On the basis of the research presented, it can be concluded that the incorporation of biocarbon into the soil generally has a positive effect on soil fertility, but that proper application is required (mainly its application together with fertilization). The quality, properties, and agricultural usefulness of the biochar depend on the raw material that has been subjected to the pyrolysis process, as well as the temperature and time of. The findings of the paper are based on the literature review on the subject.